The Influence of Environmental, Social, and Governance (ESG) on Price to Book Value (PBV), with Industry Classification as Moderation in ASEAN Companies 2013-2023 - Tokit Masditok; Tri Gunarsih; Ira Geraldina; Ake Wihadanto (UIN Sunan Gunung Djati, 2024)
This study investigates the influence of Environmental, Social, and Governance (ESG) practices on the financial performance of publicly listed companies in the ASEAN region, with a focus on Price-to-Book Value (PBV). The study further examines the moderating effect of industry sector classification, comparing heavy and non-heavy industries during the period 2013–2023. he research employs a quantitative method using secondary data in the form of unbalanced panel data. Panel data regression analysis is conducted using EViews to evaluate the effect of ESG on PBV. The analysis includes testing for moderating effects of industry sector classification (heavy vs. non-heavy sectors) using t-tests and F-tests to assess the significance of ESG’s influence on PBV. The results demonstrate a significant positive relationship between ESG and PBV in ASEAN companies. Companies with higher ESG scores tend to have higher PBV, indicating better market valuation. The study also finds that industry sector classification moderates this relationship, with non-heavy industries benefiting more from ESG practices than heavy industries, which face higher implementation costs and regulatory challenges. The findings suggest that ESG implementation can be a strategic tool for improving corporate financial performance, particularly in emerging markets like ASEAN. For heavy industries, government incentives may be necessary to offset high compliance costs. The research highlights the need for enhanced ESG disclosures and more consistent reporting standards across ASEAN to facilitate better integration of sustainability into business practices. This study fills a gap in existing literature by focusing on ASEAN, a region with unique economic and regulatory contexts. It contributes new insights into how ESG practices affect company valuation in developing markets, particularly by incorporating industry sector classification as a moderating variable, thus providing a more nuanced understanding of ESG's financial implications in diverse industrial contexts.